EXPLORING THE SUITABILITY OF FRUIT AND VEGETABLE WASTES FOR BIOMETHANE AND ELECTRICITY GENERATION (FUDMA JOURNAL OF SCIENCES, 2023)
The exploration of sustainable energy sources, such as biomethane, has become essential due to the increasing global population and demand for food and energy. This study aims to investigate the potential production of biomethane and electricity generation from fruit and vegetable waste. The fruit and vegetable waste used in this research was collected from student hostels at the College of Nursing and Midwifery, Sahaf Restaurant, Mima Restaurant, Mama Ojo Restaurant, Dan Sadi Restaurant, and IBC Restaurant in Malumfashi. The research involves laboratory analysis of the fruit and vegetable waste samples, focusing on their nutrient composition, biomethane potential, and electrical potential. Proximate analysis was used to determine the nutrient characterization, while the Baserga model was used to predict the biomethane potential. Proximate analysis revealed a total solid content of 95.92%, a volatile solid content of 86.5%, a crude protein content of 0.14%, a nitrogen-free extract of 76.96%, a crude fiber of 6.1%, and a crude fat of 3.3%. According to the Baserga model, a significant biomethane yield of 864.4 L/kg volatile solids, with a methane content of 57%, can be expected. The findings also indicate that complete degradation of fresh organic matter from fruit and vegetable waste can generate 748m3/ton of gas. Furthermore, the study predicts an electricity potential of 1601 kWh/ton of fresh fruit and vegetable waste. Based on these findings, the study recommends the use of fruit and vegetable waste as biomass for energy production to address landfilling issues and promote a more sustainable waste management approach.
Keywords: Anaerobic Digestion; Biomethane; Fruit; Vegetable wastes